Analysis of Factors Causing Moral Degradation in the Era of Technological Development in Class X Students of SMA Negeri 17 Tebo - Anggaini, Yuni; Usmanto, Heri; Ichsan, Muhammad (CV. Rayyan Dwi Bharata, 2025)
This research is motivated by student problems which in the current digital era, the development of information and communication technology has had a significant impact on student morality, especially among students. Easy access to various information via the internet and social media often exposes them to negative content that can influence behavior and moral values. Moral degradation among students characterized by deviant behavior is a major concern with factors such as lack of parental supervision, peer influence and the community environment also contributing to this phenomenon. Therefore, this research aims to analyze the causes of moral degradation in Class. This research uses a qualitative method using a descriptive approach. This research was conducted at SMA Negeri 17 and focused on teachers and students. Data collection in this research was through observation, interviews and documentation with primary data obtained from direct interviews and secondary data from related documents. The results of this research show that the occurrence of moral degradation among students at SMA Negeri 17 Tebo in the era of technological development has both positive and negative impacts. This is proven by the fact that there are still students who misuse technological developments, causing a decline in moral values including a sense of responsibility, mutual respect and the ability to make wise decisions. From the results of this research, it is recommended that schools carry out good cooperation between teachers, parents and the community to guide, supervise and educate students and that efforts are needed to ensure that technology is used appropriately so that moral values are maintained.